Homeostatic Control of Sebaceous Glands by Innate Lymphoid Cells Regulates Commensal Bacteria Equilibrium - Kobayashi, Tetsuro; Voisin, Benjamin; Kim, Do Young; Kennedy, Elizabeth A; Jo, Jay-Hyun; Shih, Han-Yu; Truong, Amanda; Doebel, Thomas; Sakamoto, Keiko; Cui, Chang-Yi; Schlessinger, David; Moro, Kazuyo; et al. (Cell, 2019)
Immune cells and epithelium form sophisticated barrier systems in symbiotic relationships with microbiota. Evidence suggests that immune cells can sense microbes through intact barriers, but regulation of microbial commensalism remain largely unexplored. Here, we uncovered spatial compartmentalization of skin-resident innate lymphoid cells (ILCs) and modulation of sebaceous glands by a subset of RORγt ILCs residing within hair follicles in close proximity to sebaceous glands. Their persistence in skin required IL-7 and thymic stromal lymphopoietin, and localization was dependent on the chemokine receptor CCR6. ILC subsets expressed TNF receptor ligands, which limited sebocyte growth by repressing Notch signaling pathway. Consequently, loss of ILCs resulted in sebaceous hyperplasia with increased production of antimicrobial lipids and restricted commensalism of Gram-positive bacterial communities. Thus, epithelia-derived signals maintain skin-resident ILCs that regulate microbial commensalism through sebaceous gland-mediated tuning of the barrier surface, highlighting an immune-epithelia circuitry that facilitates host-microbe symbiosis.